تحولات مفهوم الإنسان في فلسفة الحداثة وفلسفة ما بعد الحداثة من مأزق إنسان التأليه إلى مأزق إنسان التشويه: Transformations of the Concept of Man in the Philosophy of Modernism and Postmodernism: A Dilemma from Apotheosis to Distortion - Mostafa Kihal - كيحل مصطفى (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2019)
يعالج هذا البحث إشكالية التحولات التي تكتنف مفهوم الإنسان، لا سيما في عصر الحداثة، وعصر ما بعد الحداثة، ونـزعة الإنسية التي رسَّخت أيديولوجية التمركز حول الإنسان. وللإحاطة المنهجية والمعرفية بتلك التحولات، فقد تتبَّعنا مفهوم الأنسنة ومضامينه الفلسفية لتحديد أهم مستوياته الدلالية في بُعْدها الديني، والسياسي، والثقافي. وتمَّ استدعاء تصوُّر الإنسية الإسلامية التي لا تُمثِّل خروجاً على الدِّين، ولا تقطع مع المتعالي. كما تم تحليل المضامين الجديدة للأنسنة في مجال البيوتكنولوجيا التي أعلنت عن عصر جديد هو عصر ما بعد الانسان، الذي يتمُّ فيه التحكُّم في الحياة، والسيطرة على نقائص الطبيعة البشرية بالتقانة العلمية؛ والنظر فيما قد يترتَّب على ذلك من مخاطر على الطبيعة الإنسانية. This paper deals with the problem of the transformations that surround the concept of Man, especially in the age of modernity, postmodern, and humanism that established the ideology of human centeredness. To understand the methodology and knowledge of these transformations, we have followed the concept of humanism and its philosophical implications to determine the most important semantic levels in its religious, political, and cultural dimension. This work has called for the concept of Islamic humanism, which does not depart from religion, and does not cut off with transcendence. It also employed an analysis of the new implications of humanism in the field of biotechnology, which proclaimed a new era of post-human age in which life and defects of human nature are controlled, through scientific implications, and consider the consequent risks that may affect human nature.